2023
DOI: 10.36497/jri.v43i1.316
|View full text |Cite
|
Sign up to set email alerts
|

Change in Exhaled Volatile Organic Compounds (VOC) Profile and Interleukin-17 Serum in Lung Cancer Patient

Abstract: Background: In recent years, there have been studies regarding biomarkers for early detection of lung cancer. The expansion of tumor is accompanied by distinct metabolic process product, which results in identifiable changes in the volatile organic compounds (VOC) emission profile. The content of such molecules differs between healthy and lung cancer patients. Furthermore, the expression of Interleukin-17 (IL-17) was linked to the clinical and pathological aspects of lung cancer patients. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous study was conducted in Saiful Anwar Hospital to analyze VOC detected in lung cancer patients compared to control subjects. That study found that ethanol (C2H5OH), formaldehyde (CH2O), toluene (C7H8) and ammonia (NH3) were VOCs detected higher in lung cancer patients [17]. COPD patients have impairment of CO2 exhalation caused by increase of respiratory burden such as airway resistance and hyperinflation.…”
Section: Discussionmentioning
confidence: 95%
“…Previous study was conducted in Saiful Anwar Hospital to analyze VOC detected in lung cancer patients compared to control subjects. That study found that ethanol (C2H5OH), formaldehyde (CH2O), toluene (C7H8) and ammonia (NH3) were VOCs detected higher in lung cancer patients [17]. COPD patients have impairment of CO2 exhalation caused by increase of respiratory burden such as airway resistance and hyperinflation.…”
Section: Discussionmentioning
confidence: 95%